Emerging technologies and work-integrated learning experiences in allied health education - Singh, Indu 1961-; Raghuvanshi, Karun 1985- (IGI Global, 2018)
"This book demonstrates that standardised mix-mode of complementary various online learning tools is required to cater for student from different socio-economic and educational backgrounds and across the institutions and borders. It includes constructivist teaching methods and active learning strategies to enhance student knowledge and prepare them for the digital age"...